-5-6p=2p+2

Simple and best practice solution for -5-6p=2p+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-6p=2p+2 equation:


Simplifying
-5 + -6p = 2p + 2

Reorder the terms:
-5 + -6p = 2 + 2p

Solving
-5 + -6p = 2 + 2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-2p' to each side of the equation.
-5 + -6p + -2p = 2 + 2p + -2p

Combine like terms: -6p + -2p = -8p
-5 + -8p = 2 + 2p + -2p

Combine like terms: 2p + -2p = 0
-5 + -8p = 2 + 0
-5 + -8p = 2

Add '5' to each side of the equation.
-5 + 5 + -8p = 2 + 5

Combine like terms: -5 + 5 = 0
0 + -8p = 2 + 5
-8p = 2 + 5

Combine like terms: 2 + 5 = 7
-8p = 7

Divide each side by '-8'.
p = -0.875

Simplifying
p = -0.875

See similar equations:

| -7n+6=3(3n+10) | | 12.75x-15.35=3.124(2x+3) | | 2(5a-1)-4(-2a+3)= | | 21+9j+-10=-277 | | 1-6x=7+3x-8x | | y-(-75)=60 | | 13x-15=3(2x+3) | | 2x^3-12x^2-3x+192=0 | | 12x-15=3(2x+4) | | 8c=54 | | 7n+2n=81 | | 27x-1=19x+14+5x | | 4c-5+14c= | | 13=4x+-11 | | x/3=-19 | | 2(x+8)-4=2(x-7)+8 | | x-5[2x-3(x+6)]=-4(x-5) | | -11.3x=101.7 | | 3y+6=y^2 | | =6t | | 2.5-4f=10-2.5f | | (X+10)=(2x+5) | | =10y-15y | | -10=(a-1)+(a-3) | | 28=m-4 | | x^3-16y=0 | | -4(2b+1)+(9b-7)=0 | | 7j-25=2j | | 3x+1-3x-3x-1=45 | | 6+2m=-3+5m | | x^4-6x^3+10x^2-9=0 | | x^2+(3x^2-30x+25)=25 |

Equations solver categories